Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Discover a wealth of knowledge from professionals across various disciplines on our user-friendly Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To solve the problem, we need to determine the value of [tex]\( (f-g)(144) \)[/tex].
Let's start by evaluating the functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] at [tex]\( x = 144 \)[/tex].
First, consider the function [tex]\( f(x) = \sqrt{x} + 12 \)[/tex]:
1. Find [tex]\( f(144) \)[/tex]:
[tex]\[ f(144) = \sqrt{144} + 12 \][/tex]
Since [tex]\( \sqrt{144} = 12 \)[/tex]:
[tex]\[ f(144) = 12 + 12 = 24.0 \][/tex]
Next, consider the function [tex]\( g(x) = 2 \sqrt{x} \)[/tex]:
2. Find [tex]\( g(144) \)[/tex]:
[tex]\[ g(144) = 2 \sqrt{144} \][/tex]
Since [tex]\( \sqrt{144} = 12 \)[/tex]:
[tex]\[ g(144) = 2 \cdot 12 = 24.0 \][/tex]
Finally, to find [tex]\( (f-g)(144) \)[/tex], we subtract [tex]\( g(144) \)[/tex] from [tex]\( f(144) \)[/tex]:
3. Calculate [tex]\( (f-g)(144) \)[/tex]:
[tex]\[ (f-g)(144) = f(144) - g(144) = 24.0 - 24.0 = 0.0 \][/tex]
Therefore, the value of [tex]\( (f-g)(144) \)[/tex] is [tex]\( 0 \)[/tex].
So, the correct answer is:
[tex]\[ \boxed{0} \][/tex]
Let's start by evaluating the functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] at [tex]\( x = 144 \)[/tex].
First, consider the function [tex]\( f(x) = \sqrt{x} + 12 \)[/tex]:
1. Find [tex]\( f(144) \)[/tex]:
[tex]\[ f(144) = \sqrt{144} + 12 \][/tex]
Since [tex]\( \sqrt{144} = 12 \)[/tex]:
[tex]\[ f(144) = 12 + 12 = 24.0 \][/tex]
Next, consider the function [tex]\( g(x) = 2 \sqrt{x} \)[/tex]:
2. Find [tex]\( g(144) \)[/tex]:
[tex]\[ g(144) = 2 \sqrt{144} \][/tex]
Since [tex]\( \sqrt{144} = 12 \)[/tex]:
[tex]\[ g(144) = 2 \cdot 12 = 24.0 \][/tex]
Finally, to find [tex]\( (f-g)(144) \)[/tex], we subtract [tex]\( g(144) \)[/tex] from [tex]\( f(144) \)[/tex]:
3. Calculate [tex]\( (f-g)(144) \)[/tex]:
[tex]\[ (f-g)(144) = f(144) - g(144) = 24.0 - 24.0 = 0.0 \][/tex]
Therefore, the value of [tex]\( (f-g)(144) \)[/tex] is [tex]\( 0 \)[/tex].
So, the correct answer is:
[tex]\[ \boxed{0} \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.